2020
DOI: 10.3390/nu12092720
|View full text |Cite
|
Sign up to set email alerts
|

Milk Consumption for the Prevention of Fragility Fractures

Abstract: Results indicating that a high milk intake is associated with both higher and lower risks of fragility fractures, or that indicate no association, can all be presented in the same meta-analysis, depending on how it is performed. In this narrative review, we discuss the available studies examining milk intake in relation to fragility fractures, highlight potential problems with meta-analyses of such studies, and discuss potential mechanisms and biases underlying the different results. We conclude that studies e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 157 publications
(206 reference statements)
1
2
0
Order By: Relevance
“…The repeated measurements allowed us to time-update information on exposures and covariates and thus capture diet and lifestyle changes and acquire higher precision and accuracy than with one (baseline) measurement only. As in our study, another Swedish study observed a decreased consumption of milk and an increased consumption of fermented milk over time [ 20 ], reflecting societal trends in consumption [ 21 ]. Another strength is the ascertainment of stroke diagnosis not only for total stroke but also for cerebral infarction and hemorrhagic stroke without loss to follow-up since we could individually link all participants to the national patient and cause of death registries.…”
Section: Discussionsupporting
confidence: 76%
“…The repeated measurements allowed us to time-update information on exposures and covariates and thus capture diet and lifestyle changes and acquire higher precision and accuracy than with one (baseline) measurement only. As in our study, another Swedish study observed a decreased consumption of milk and an increased consumption of fermented milk over time [ 20 ], reflecting societal trends in consumption [ 21 ]. Another strength is the ascertainment of stroke diagnosis not only for total stroke but also for cerebral infarction and hemorrhagic stroke without loss to follow-up since we could individually link all participants to the national patient and cause of death registries.…”
Section: Discussionsupporting
confidence: 76%
“…It is important to highlight that milk contains calcium and basic nutrients such as protein, magnesium, phosphorus, potassium and vitamin K2 (G orska-Warsewicz et al 2019). Calcium is essential for the growth and development of bones, and being an excellent source of calcium, milk is essential for optimum bone health and can help in preventing bone diseases like osteoporosis and fractures (Feskanich et al 2018;Mat ıa-Mart ın et al 2019;Byberg and Warensj€ o Lemming 2020). Moreover, milk is a good source of proteins, which makes up 50% of the bone volume and a third of the total bone mass.…”
Section: Nutrients In Milk and Healthmentioning
confidence: 99%
“…2018; Matía‐Martín et al . 2019; Byberg and Warensjö Lemming 2020). Moreover, milk is a good source of proteins, which makes up 50% of the bone volume and a third of the total bone mass.…”
Section: Nutrients In Milk and Healthmentioning
confidence: 99%